Palabra y sabiduría africana en Babá Osaím, cimarrón, ora por la santa muerta de Cronwell Jara Jiménez - de Lima, Paolo (2024)
This paper examines the short-story collection titled Babá Osaím, cimarrón, ora por la santa muerta (1989), by Peruvian writer Cronwell Jara Jiménez (Piura, 1949). Specifically, it concentrates on the linguistic, cultural and religious elements of the texts that are related to the way in which the harsh experiences of the black population in colonial times are represented, as well as those that directly address this social universe in relation to concrete references to the African continent. Through these stories, Jara’s book presents characters who confront oppression and slavery while keeping their African roots alive. It is thus a literary testimony that explores the cultural conditions in which African worldview and spirituality developed during colonial times, as well as their influence on colonial Peru. Our analysis will take into account ideas of the Kenyan writer Ngũgĩ wa Thiong’o, from his book Decolonizing the mind (1981), and of the Costa Rican literary critic of Afro origin Quince Duncan and his concept of “literary afrorrealism”, while the book’s proposal will be confronted with the Uruguayan critic Ángel Rama’s approaches to “narrative transculturation”.